Variasi Morfometri Ikan Botia (Botia macracanthus Bleeker) dari Perairan Sumatera Dan Kalimantan - Sudarto Sudarto; Muhammad Rizal (Universitas Gadjah Mada, 2007)
The objective of the research was to find out the differences between two populations of botia (Botia macracanthus Bleeker) from Sumatera and Kalimantan waters analized using morphometric characters. Two populations of botia from Sumatera and three populations from Kalimantan waters were collected and analyzed their distance of phylogenic relationships mostly based on the morphometric characters. There were 30 numbers of morphometrics characters measured, and 5 numbers of meristic characters were counted and 2 numbers additional information were collected. Botia from Kalimantan was physically longer than that from Sumatera.The result showed that both of botia were significantly differents from each others. The phylogenic relationships was found as fuction of Z = -3,367-0,866DSL-0,585IOW-0,757AFL+0,261PESL-0,429 PPL+0,756PPEL+0,175PAL+0,417MBD.